Doing Business in a Transitional Society: Economic Environment and Relational Political Strategy for Multinationals. (September 2013) - Luo, Yadong; Zhao, Hongxin
This article addresses how foreign subsidiaries formulate their relational political strategy by responding to the unique parameters of the economic and institutional environment in an emerging market in an attempt to improve their performance. To this end, the authors have developed a model that assesses economic environment antecedents characterizing an emerging market (regulatory distance, industry accessibility, environmental uncertainty, and economic development) as well as the performance consequence of the subsidiaries' relational political strategy. A possible moderating effect of the firm's reputation in the host country and length of operations on the relationship between political strategy and local performance is also examined in the model. Our analysis of primary and secondary data concerning 358 foreign-invested enterprises in China generally supports this model.